Development of Children's Storybooks Based on Bima Local Wisdom to Enhance Cultural and Reading Literacy in Fifth Grade Elementary School - Nur Afni; I Gede Margunayasa; I Made Citra Wibawa (STKIP Taman Siswa Bima, 2025)
The limited availability of reading materials that highlight local culture in elementary schools has led to low cultural literacy and reading skills among students. Therefore, this study aims to develop a Bima local wisdom-based children's storybook as a learning medium to enhance the cultural literacy and reading skills of fifth-grade students. The storybook was developed using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The research subjects included fifth-grade students of SDN Inpres Tente, classroom teachers, and experts in content, media, and language involved in the product validation process. The research object was the children's storybook La Lino and La Mango, which integrates cultural and moral values of the Bima community. Data collection methods included observations, interviews, questionnaires, tests, and documentation. The findings indicate that the storybook has a very high level of validity, with scores of 4.15 for content aspects and 4.0 for media aspects. The practicality test conducted by teachers yielded a score of 4.9, indicating that the book is easy to use in learning. Meanwhile, the effectiveness test using the n-gain score showed a significant improvement in students' cultural literacy and reading skills. Thus, the Bima local wisdom-based children's storybook serves as an innovative learning medium that not only enhances students' literacy but also introduces and preserves local culture.